1994
DOI: 10.1002/jctb.280610408
|View full text |Cite
|
Sign up to set email alerts
|

Removal of phenol from coupling of talc and peroxidase. Application for depollution of waste water containing phenolic compounds

Abstract: The degradation of phenol by a combination of horseradish peroxidase/hydrogen peroxide in the presence of talc, a natural abundant and low cost mineral, was investigated. Adsorption of the reaction products on the talc effectively protected the biocatalyst against contamination by oxidative products, thereby prolonging its catalytic action and leading to almost complete elimination of phenols in aqueous media. Suitable conditions for depollution of waste water containing phenolic substances were developed afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 2 publications
1
17
0
Order By: Relevance
“…Specifically, the use of plant peroxidases in removal of phenolic pollutants from aqueous solution is well documented [19,20]. It has been demonstrated that horseradish peroxidase (HRP) can catalyze free-radical formation, followed by spontaneous polymerization of a variety of aromatic compounds, including phenol [21][22][23][24], chlorophenols [13,25] and other substituted phenols [26], in the presence of hydrogen peroxide (H 2 O 2 ). Furthermore, HRP is also known to have the ability to degrade aromatic azo compounds in the presence of H 2 O 2 and to precipitate industrially important azo dyes [15,16,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the use of plant peroxidases in removal of phenolic pollutants from aqueous solution is well documented [19,20]. It has been demonstrated that horseradish peroxidase (HRP) can catalyze free-radical formation, followed by spontaneous polymerization of a variety of aromatic compounds, including phenol [21][22][23][24], chlorophenols [13,25] and other substituted phenols [26], in the presence of hydrogen peroxide (H 2 O 2 ). Furthermore, HRP is also known to have the ability to degrade aromatic azo compounds in the presence of H 2 O 2 and to precipitate industrially important azo dyes [15,16,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Considerable efforts have aimed at optimizing the HRP-catalyzed removal of phenols from aqueous solutions. Improvements in the useful life of the enzyme, and thereby a reduction in treatment cost, have been accomplished through: selection of an appropriate reactor configuration (Nicell et al, 1993b); the use of additives such as polyethylene glycol to protect the enzyme from premature inactivation (Nakamoto and Machida, 1992); the addition of absorbents such as talc which protect the enzyme from inhibition by reaction products (Arseguel and Baboulène, 1994); and the immobilization of the enzyme on solid supports (Bodzek et al, 1994). In particular, the advantages of immobilization for enzymes can include the preservation of enzyme activity (Coppella et al, 1990), the potential for continuous flow treatment (Caldwell and Raushel, 1991) and the possibility of enzyme reuse (Munnecke, 1977).…”
Section: (A) Aromatic Pollutantsmentioning
confidence: 99%
“…[8][9][10][11][12]. These methods are effective in removing the pollutants with limitations of being expensive, time consuming, and low efficiency, applicability to a limited concentration range and formation of soluble toxic by-products [13][14][15].…”
Section: Introductionmentioning
confidence: 99%